The Oxford Handbook of Historical Political Economy 2022
DOI: 10.1093/oxfordhb/9780197618608.013.10
|View full text |Cite
|
Sign up to set email alerts
|

Dynasties in Historical Political Economy

Abstract: The hereditary transfer of political power within families is a prominent feature of premodern societies and persists in some form even in modern democracies. This chapter reviews the role of dynasties in the historical development of states and how patterns in dynastic politics serve as a useful metric for understanding the evolution of power and state organization in historical political economy research. The chapter identifies and describes three broad declines in the role of dynasties in politics: (1) a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Beyond these electoral advantages, dynasty members also benefit from career advantages. Dynastic members are more likely to be appointed to cabinet, but only if their previous relatives have been appointed to cabinet as well (Smith and Martin 2017;Van Coppenolle 2017;Van Coppenolle and Smith 2022). We expect the dynasty-cabinet link to be a relevant factor in Canada, as it is in Ireland (Smith and Martin 2017) and the UK (Van Coppenolle 2017).…”
Section: Political Family Dynastiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Beyond these electoral advantages, dynasty members also benefit from career advantages. Dynastic members are more likely to be appointed to cabinet, but only if their previous relatives have been appointed to cabinet as well (Smith and Martin 2017;Van Coppenolle 2017;Van Coppenolle and Smith 2022). We expect the dynasty-cabinet link to be a relevant factor in Canada, as it is in Ireland (Smith and Martin 2017) and the UK (Van Coppenolle 2017).…”
Section: Political Family Dynastiesmentioning
confidence: 99%
“…Indeed, research on this topic has confirmed that offspring follow their parents into politics in larger numbers than in the general population, with the exception of farming and self-employed proprietors (Dal Bó et al 2009;Laband and Lentz 1985). The implications suggest that dynasties provide potential legislators with a series of advantages ranging from skill transfer, voter loyalty, incumbency advantage and name recognition (Feinstein 2010;Fiva and Smith 2018;Geys 2017;Laband and Lentz 1985;Smith and Martin 2017;Van Coppenolle and Smith 2022). In the US, David Laband and Bernard Lentz (1985) argue that being part of a dynasty might make 'politics' a hereditary skill, providing the legislator with voter loyalty and a higher degree of incumbency advantage than would normally be enjoyed by legislators who are not part of a dynasty.…”
Section: Political Family Dynastiesmentioning
confidence: 99%
See 3 more Smart Citations